Natural Killer Cell Engagers (NKCEs): a new frontier in cancer immunotherapy - Zhang, Minchuan; Lam, Kong-Peng; Xu, Shengli (Frontiers in Immunology, 2023)
Natural Killer (NK) cells are a type of innate lymphoid cells that play a crucial role in immunity by killing virally infected or tumor cells and secreting cytokines and chemokines. NK cell-mediated immunotherapy has emerged as a promising approach for cancer treatment due to its safety and effectiveness. NK cell engagers (NKCEs), such as BiKE (bispecific killer cell engager) or TriKE (trispecific killer cell engager), are a novel class of antibody-based therapeutics that exhibit several advantages over other cancer immunotherapies harnessing NK cells. By bridging NK and tumor cells, NKCEs activate NK cells and lead to tumor cell lysis. A growing number of NKCEs are currently undergoing development, with some already in clinical trials. However, there is a need for more comprehensive studies to determine how the molecular design of NKCEs affects their functionality and manufacturability, which is crucial for their development as off-the-shelf drugs for cancer treatment. In this review, we summarize current knowledge on NKCE development and discuss critical factors required for the production of effective NKCEs. List of abbreviations 30 ADCC Antibody-dependent cellular cytotoxicity ADCP Antibody-dependent cellular phagocytosis AICL Activation-induced C-type lectin AML Acute myeloid leukemia BCMA B-cell maturation antigen BiKE Bispecific killer cell engager CAR Chimeric antigen-receptor CDC Complement-dependent cytotoxicity CDR Complementarity-determining regions CHO Chinese hamster ovary CLEC12A C-type lectin domain family 12 member A CMV Human cytomegalovirus CRS Cytokine release syndrome CS1 CD2 subset-1 CTLA4 Cytotoxic T-lymphocyte-associated antigen-4 DAP10/ DAP12 DNAX-activating protein of 10kDa/12kDa